Gender dan Tradisi Living Qur’an: Praktik Keagamaan di Desa Maesan, Kabupaten Bondowoso (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This study aims to explore the dynamics of religious practices based on the Living Qur’an tradition and the gender relations embedded within it in Maesan Village, Bondowoso Regency. The main focus of this research is to understand how women interpret and carry out religious roles within local traditions rooted in Qur’anic values. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, participatory observation, and documentation involving religious leaders, women in Qur’anic study groups, and community figures. The findings reveal that Living Qur’an practices such as tahlilan, yasinan, and khataman not only serve as spiritual expressions but also act as strategic spaces for women to build social roles and active participation within the community. These practices demonstrate a transformation in gender relations that does not negate Islamic values but instead affirms the authenticity of Islam through contextual and inclusive expressions. The implications of this research highlight the importance of strengthening women’s religious participation in community-based Islamic traditions while opening further scholarly discussions on reconstructing women's religious roles amid social change. This study also contributes to the development of contextual Islamic studies and gender discourse within the framework of local culture.